2009
DOI: 10.1534/genetics.108.095190
|View full text |Cite
|
Sign up to set email alerts
|

The Decay of the Chromosomally Encoded ccdO157 Toxin–Antitoxin System in the Escherichia coli Species

Abstract: The origin and the evolution of toxin-antitoxin (TA) systems remain to be uncovered. TA systems are abundant in bacterial chromosomes and are thought to be part of the flexible genome that originates from horizontal gene transfer. To gain insight into TA system evolution, we analyzed the distribution of the chromosomally encoded ccd O157 system in 395 natural isolates of Escherichia coli. It was discovered in the E. coli O157:H7 strain in which it constitutes a genomic islet between two core genes ( folA and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 34 publications
1
56
0
Order By: Relevance
“…A previous study indicated that chromosomally carried ccd operons undergo a decay process within the E. coli species and therefore are likely to lose their antiaddictive property, with about 29% of the strains harboring an inactive toxin (12). The present work suggests a probable explanation for the presence of an active ccd operon in more than 69% of the E. coli strains studied, namely, that they functionally integrate into the host regulatory network, leading to enhanced tolerance to multiple antibiotics through the formation of persisters.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…A previous study indicated that chromosomally carried ccd operons undergo a decay process within the E. coli species and therefore are likely to lose their antiaddictive property, with about 29% of the strains harboring an inactive toxin (12). The present work suggests a probable explanation for the presence of an active ccd operon in more than 69% of the E. coli strains studied, namely, that they functionally integrate into the host regulatory network, leading to enhanced tolerance to multiple antibiotics through the formation of persisters.…”
Section: Discussionmentioning
confidence: 50%
“…There are different models that have been proposed to explain their presence on the chromosome. For the chromosomal ccd systems, these include the antiaddiction model (11), which states that the chromosomally encoded ccd system (ccd Ech ) protects the cell against postsegregational killing mediated by its F-plasmid ccd (ccd F ) homolog, whereas for the ccd O157 system, it has been suggested that this system is devoid of any biological role in the E. coli species (12). Models proposed for other chromosomal TA systems include the programmed cell death (PCD) model, the growth modulation model, the persistence model, and the development model (13).…”
Section: Abstract Toxin-antitoxin Persistencementioning
confidence: 99%
See 1 more Smart Citation
“…ZP_01978533). The sequence of the chromosomal ccd systems have diverged significantly from the F-plasmid ccd operon studied here, although in ∼70% of cases both components of the chromosomal ccd have retained their toxic activity (26). Molecular evolutionary analysis of 47 isolates of ccdB 0157 suggested that the chromosomally encoded ccdAB TA systems appear devoid of any biological function and are under neutral evolution (26).…”
Section: Discussionmentioning
confidence: 82%
“…Therefore, various chromosomal TAs may be the result of a specific arms race with their plasmid-encoded counterparts. However, when plasmidic TA systems 'escape' from this control (Saavedra De Bast et al, 2008;Mine et al, 2009;Rankin et al, 2012), the latter may undergo progressive degeneration and eventually disappear, unless they become incorporated into the cell's physiological processes, such as programmed cell death or persistence (Mine et al, 2009). …”
Section: Q B Io S Y N T H E S Is P R O T E In H Y P O T H E T Ic a L mentioning
confidence: 99%